Analisis Hubungan Antara Tingkat Pengangguran dan Fenomena Mismatch Pekerjaan Dengan Jurusan di Indonesia: Analysis of the Relationship Between Unemployment Rates and Job Mismatch Phenomena with Majors in Indonesia - Arya Rio Pratama Putra; Muhamad Aldi Triwijaya; Raehan Langitan; Safwan Zacky Fianto; Rudianto Rudianto (CV Warnak Johanna Nusantara, 2026)
Abstract - The purpose of this observation is to examine the relationship between unemployment rates in Indonesia and the mismatch between job types and academic disciplines. Mismatch is understood as the mismatch between educational qualifications obtained and job requirements. This phenomenon is increasingly relevant given the dynamics of the job market that demand adaptive competencies, resulting in many graduates finding it difficult to be absorbed ideally. This observation applies a measurement system and online survey through Google Forms, involving participants from various educational and employment contexts. The information collected is analyzed to identify patterns of mismatch and their contribution to the likelihood of individuals experiencing unemployment. The purpose of this study is to analyze the influence of these three factors, both partially and simultaneously, on the unemployment rate. The method used is quantitative with a questionnaire instrument, analyzed through validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and determination coefficients. The results of the study show that job mismatch has a positive and significant effect on the unemployment rate (Sig. 0.000). Thus, the higher the mismatch between educational majors and jobs, the greater the likelihood of college graduates experiencing unemployment.